Evolution of game-play characteristics within-season for the National Basketball Association - Zhang, S.; Lorenzo, A.; Woods, C. T.; Leicht, A. S.; Gomez, M.-A. (International Journal of Sports Science & Coaching, 2019)
The aim of this study was to explore the (dis)similarity of game-play characteristics throughout an in-season period within the National Basketball Association. Thirteen performance-related indicators of all 1230 games of the regular 2016-2017 season in the National Basketball Association were analysed. Non-metric multidimensional scaling was used to examine (dis)similarity of team profiles. The two-dimensional multivariate matrix showed that team profiles generally presented similarity, while the beginning and ending of the season (October and April) showed relative dissimilarity. Although each team presented unique paths throughout the in-season period, the dominant teams in the National Basketball Association presented similar game styles. In addition, the game-play of the teams evolved into effective interactions in terms of offence and defence as the competition progressed while presenting an increased trend in the number of three-point field-goals made (p < 0.000, small effect size ( n2) = 0.011) throughout the in-season period. The analytics performed in this study could be used practically to evaluate temporal changes of game-play characteristics in basketball as well as inform strategic periodization plans within season periods.